1970
DOI: 10.1136/jnnp.33.4.528
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of paroxysmal disorders in multiple sclerosis with carbamazepine (Tegretol)

Abstract: SUMMARY During an eight year period, 32 patients with definite or suspected multiple sclerosis (MS) were seen with paroxysmal neurological disturbances, which included tonic seizures, paroxysmal dysarthria, paraesthesiae and pain in the limbs, as well as trigeminal neuralgia. In 21 of these patients the paroxysmal disorders were treated with carbamazepine, and in six the effect was compared with placebo. In the majority carbamazepine was effective in controlling the paroxysmal symptoms. Side-effects were troub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

1974
1974
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(43 citation statements)
references
References 8 publications
3
38
0
2
Order By: Relevance
“…Controlled clinical trials have suggested that carbamazepine is helpful for paroxysmal pain syndromes, including TN. 18,19 Other studies, generally small open-label trials and observational studies, suggest that gabapentin reduces pain 20,21 and that misoprostol may also be effective. 22 Thus, many of the therapies tried by the present study population have not been shown to be effective for TN.…”
Section: Resultsmentioning
confidence: 99%
“…Controlled clinical trials have suggested that carbamazepine is helpful for paroxysmal pain syndromes, including TN. 18,19 Other studies, generally small open-label trials and observational studies, suggest that gabapentin reduces pain 20,21 and that misoprostol may also be effective. 22 Thus, many of the therapies tried by the present study population have not been shown to be effective for TN.…”
Section: Resultsmentioning
confidence: 99%
“…The symptoms typically respond well to carbamazepine. 14 It is unclear what mechanism caused involuntary tonic spasms in the paretic limb of this patient with a pontine lacunar infarction. The absence of any change on the EEG during a typical spell argues against an epileptic phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Four patients (1,8,9 and 10) had clinically definite MS, four (11)(12)(13)(14) latent MS and the remaining six (2-7) suspected MS, according to …”
Section: Patientsmentioning
confidence: 99%